Innovative Approaches to Providing Outdoor Education for Handicapped Students. Outdoor Education for the Handicapped - Kentucky Univ., Lexington; Kentucky Univ., Lexington ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
This publication describes 12 outdoor education programs/centers serving persons with disabilities in their program curriculum. Each program is described in detail and each description includes an overview of purposes and goals, facility/site description, administration structure, program emphasis for disabled populations, and source of funding and annual operating budgets. The programs are geographically representative of the United States and incorporate "state-of-the-art" techniques/approaches utilized for outdoor education program planning development and implemented for the disabled. Included are examples of mainstreamed and segregated programs serving all types and ages of disabled persons in either residential or day programs. There are also examples of cooperative approaches to program design/development utilizing parents of disabled children, educators, and park and resource management personnel as members of planning teams. Other programs describe techniques used for fundraising and integrating outdoor education into the overall curriculum. Programs described are Babler Outdoor Education Center for the Handicapped; Bradford Woods Outdoor Education, Recreation and Camping Center; Camp Confidence; Colorado Outdoor Education Center for the Handicapped; Courage Center Outdoor Education Programs; Eckerd Wilderness Education System Camping Program; Georgia State Camping Program for the Handicapped; Lathrope E. Smith Environmental Education Center; Minnesota Outward Bound; Mt. Hood Kiwanis Camp; Nassau BOCES Outdoor and Environmental Education Program; and Santa Fe Mountain Center. (NEC)
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC. Div. of Innovation and Development.
Contract Number: 6007903300.
ERIC Note: A product of the Outdoor Education for the Handicapped Project. For related documents, see RC 015 878-880.
Educational level discussed: Adult Education.
Educational level discussed: Elementary Secondary Education.
Practitioners.
Keywords: Administration; Adult Education; Budgets; Cooperative Planning; Curriculum; Day Programs; Disabilities; Educational Innovation; Educational Objectives; Elementary Secondary Education; Experiential Learning; Facilities; Financial Support; Mainstreaming; Outdoor Education; Program Descriptions; Residential Programs; Special Education; Reports, Descriptive; Guides, Non-Classroom.